Environmental Source of Candida dubliniensis - Miles A. Nunn; Stefanie M. Schäfer; Michael A. Petrou; Jillian R.M. Brown (Emerging Infectious Diseases, 2007)
We isolated Candida dubliniensis from a nonhuman source, namely, tick samples from an Irish seabird colony. The species was unambiguously identified by phenotypic and genotypic means. Analysis of the 5.8S rRNA gene showed that the environmental isolates belong to C. dubliniensis genotype 1.